An Assessment of the Drivers of Wetlands Transformation in Kisii Town, Kenya - Osoro, Fredrick Bosire; Okotto, Lorna Grace; Awuor, Frankline Otiende (International Journal of Research and Innovation in Social Science, 2025)
Wetlands are areas of importance according to Ramsar Convention. However, they are increasingly under threat as a result of unwise utilization which leads to undesired transformation. The study sought to assess how wetlands have been transformed, find out the main drivers of transformation, to establish the current status of natural wetlands and to explore stakeholder’s recommendations on mitigation and rehabilitation measures of the affected wetlands in Kisii town. The target population was 440 households whose land parcels were adjacent to the wetlands of study, 7 Key informants and farmers divided into two groups for discussions. The methodology entailed use of stratified random sampling and data was collected by use of questionnaires, document reviews, interviews, group discussions and observation. Data from questionnaire were cleaned, coded and then fed into the Statistical Package for Social Sciences (SPSS) version 20 and Microsoft Excel version 2010. The analysis was then accomplished through the computation of frequencies and percentages that are presented in form of tables and figures to facilitate further interpretation, the rest of the data were analyzed through content analysis. Results indicate that 60% of the respondents were of the view that wetlands in the study area have been degraded and there have been little or no efforts of rehabilitation and restoration. The study further found out that considerable loss of biodiversity had been occasioned by negative wetland transformation. It was found out that the main drivers of wetlands transformation in Kisii town are massive development activities (15.8%), invasive species (12.5%) and overgrazing by livestock (12.5%). The study recommends that 1) Government agencies should focus on mitigation programmes to deter further degradation through multi-sectoral approach, 2) establishment of a one stop development approval center by the County government to deter development on riparian and wetland areas, and 3) gazettement of wetland areas for conservation activities. These can be achieved through formulation of wetland policy for Kisii as a County to take care of the existing policy gaps
Keywords: Wetlands; Drivers of Transformation; Conservation; Policy Awareness; Kisii Town